Dance in Opera in London, 1673–1685. (November 2015) - Thorp, Jennifer
Abstract : This article looks at the extent to which French styles of theatrical dancing influenced opera in London during the years 1673–1685. In the 1670s the emergence of opera in London owed much to Stuart Court culture and its interest in French ballets de cour and English masques. Meanwhile on the London stage in the 1670s, English theatrical dance was now enhanced by the ability of the Duke of York's new theatre at Dorset Garden to offer the sort of spectacular staging already known in Paris and which suited opera so well. These influences – the love of French music and dancing as balanced by the continued interest in vernacular theatre and its new capacity for spectacle – resulted in an English approach to opera in which the dancing and scenography rarely remained completely French or completely English. This article considers opera dancing in London, from the addition of dance to a reworked Shakespeare play in 1673, followed the next year by the first opera sung in French to be staged in London, and the sometimes hybrid applications of English and French dance in opera thereafter. That the fascination with French opera had diminished after 1685 is reinforced by the unsuccessful attempt to stage one of Lully's tragédies-en-musique in a London theatre the following year.